1984
DOI: 10.5271/sjweh.2292
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism and occupation.

Abstract: , MD1OLKINUORA M. Alcoholism and occupation. Scand J Work Environ Health 10 (1984) 51 1-5 15. Occupational roles are a dominant force in many aspects of social life. Occupation signifies a complex of social and psychological factors that reflect intelligence, education, personality, ambition, social status, and life-style. The consumption of alcohol and alcoholism have many correlations with occupational roles. Mortality from cirrhosis of the liver reflects the per capita consumption of alcohol. In certain occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…The following occupations with an elevated risk of alcoholism in this study have previously been associated with a high risk of alcoholism in studies from different countries (mainly Great Britain and the United States) among men: seamen (1,3,7,15,16,(18)(19)(20), construction workers (3-5, 7), painters (3), bricklayers (7), sheetmetal workers (7), and waiters (2, 7). Among women an increased risk has been reported for waitresses (5,7).…”
Section: Comparison With Previous Studies On Occupation and Alcoholismmentioning
confidence: 65%
See 1 more Smart Citation
“…The following occupations with an elevated risk of alcoholism in this study have previously been associated with a high risk of alcoholism in studies from different countries (mainly Great Britain and the United States) among men: seamen (1,3,7,15,16,(18)(19)(20), construction workers (3-5, 7), painters (3), bricklayers (7), sheetmetal workers (7), and waiters (2, 7). Among women an increased risk has been reported for waitresses (5,7).…”
Section: Comparison With Previous Studies On Occupation and Alcoholismmentioning
confidence: 65%
“…Several studies have shown differing rates of alcoholism between occupations (1)(2)(3)(4)(5)(6)(7)(8). It is often concluded that blue-collar occupations have higher rates of alcoholism when compared with white-collar occupations, while those outside the labor market are at the highest risk.…”
mentioning
confidence: 99%
“…Proportionate mortality studies of construction workers in the U.S. reveal excess deaths from diagnoses associated with alcohol abuse [Robinson et al, 1995;Wang et al, 1999]; and alcohol-related use of health services, both inpatient and outpatient, has been reported to be among the highest in males who do construction work [Olkinuora, 1984]. Individuals in the construction trades have among the highest rates of occupational injury [Kisner and Fosbroke, 1994;.…”
Section: Individuals In the Construction Trades In The Unitedmentioning
confidence: 99%
“…Recent national survey data in the United States report high rates of alcohol and substance abuse among individuals in the construction trades [Hoffmann et al, 1996] and proportionate mortality studies of construction workers in the United States reveal excess deaths from diagnoses associated with alcohol abuse [Robinson et al, 1995;Wang et al, 1999]. In addition, alcohol-related use of health services, both inpatient and outpatient, has been reported to be among the highest in males who do construction work [Olkinuora, 1984].…”
Section: Introductionmentioning
confidence: 99%